ANALISIS DIKSI KONOTATIF DALAM NOVEL KONBINI NINGEN KARYA SAYAKA MURATA : SEBUAH KAJIAN SEMANTIK - Ahmad Hilmi Fuadi; Komara Mulya; Frida Philiyanti (Universitas Negeri Jakarta, 2026)
This study analyzes the use of connotative diction in Sayaka Murata’s Konbini Ningen using a semantic approach. It aims to identify the meanings and types of connotative diction employed by the author. Through a descriptive qualitative method, data were collected by observing and noting expressions in the original Japanese text. The analysis applies Sutedi’s (2003) theory of connotative semantic features (imitokuchou) and Chaer’s (2009) classification of connotative diction. Of the 40 data found, 12 are positive, 25 negative, and 3 neutral. Negative connotations dominate, reflecting the protagonist’s alienation, inner conflict, and social critique. Positive ones appear in moments of self-acceptance, while neutral ones describe emotionally balanced states. The findings show that connotative diction effectively conveys psychological depth and social commentary. This research highlights how linguistic choices shape literary meaning and suggests further studies on other semantic aspects for deeper interpretation.